Characterizing fine-scale spatiotemporal variations in canopy litterfall and fine root dynamics in cool temperate forest ecosystems - Mark Bryan Carayugan; Ji Young An; Byung Bae Park (Global Ecology and Conservation)
Aboveground canopy and fine roots, two key allocations of autotrophic productivity in forest ecosystems, create a dynamic pathway for carbon and nutrient entry into the soil during senescence and decomposition. Despite their relevance, little is known about the local factors influencing canopy litter and fine root variability, both within stands and across years, which hampers our understanding of plant mineral nutrient status in cool temperate environments. This study combined up to four years of field measurements (2–4 years for litterfall, 1 year for fine root stocks, and 2 years for fine root production and mortality) from twelve 0.02–0.09-ha stands in Gwangneung Experimental Forest to investigate the relationships between litter and fine root variability and stand topographic, structural, and edaphic features. Topography emerged as a key driver of variation within stands, significantly influencing total litterfall (βstd.= −0.568 for elevation; βstd.= −0.597 for slope), leaf litterfall (βstd.= −0.722 for elevation), total fine root biomass (βstd. = −0.863 for slope), and < 1mm-sized root biomass (βstd.= −0.618 for slope). Miscellaneous litter exhibited less variability within stands as the basal area increased. Soil magnesium content positively correlated with within-stand fine root biomass variation at depths of 15–30 cm but exhibited an inverse relationship with fine root necromass variation at 5–10 cm. Within-stand variability of fine root mortality increased with soil organic matter, highlighting its critical role in nutrient bioavailability. Our findings underscore the importance of local environmental factors in shaping the spatiotemporal variability of litter and fine roots, offering insights into the carbon and nutrient cycling in cool temperate forests amid environmental change.